ANALISIS KONSEP ADAP DAN AKHLAK DALAM MENUNTUT ILMU MENURUT BAKR BIN ABDULLAH SERTA RELEVANSINYA TERHADAP PENDIDIKAN MODERN DI INDONESIA - Robi'ah Robi'ah; Agus Supriadi (Jurnal Cinta Nusantara, 2026)
This study aims to determine Bakr Bin Abdullah's views on the meaning of morality in seeking knowledge according to Bakr Bin Abdullah, and to what extent its relevance to morality in seeking knowledge in the context of modern education. The data for this study are the book Sarah Hilyah Thalibil ilmi and other books related to the demands of moral knowledge. The data collected were then analyzed by content analysis or content analysis. Next, they were categorized (grouped) with similar data, and the contents were analyzed critically in order to obtain a concrete and adequate formulation, so that finally it was used as a step in drawing conclusions as an answer to the existing problem formulation. The results of the study are, according to Bakr Bin Abdullah, the morality of the demands of knowledge according to Bakr Bin Abdullah is (1). Knowledge is worship; (2). Walking on the manhaj salafussaleh, following in the footsteps of the Prophet; (3). Fearing Allah; (4). Embracing murokobah, adorning yourself with always feeling feared by Allah; (5). be humble, destroy arrogant and arrogance; (6). Qonaah and asceticism; (7). adorn yourself with the beauty of knowledge.